فاعلية برنامج تدريبي للوالدين قائم على تحليل السلوك التطبيقي في تحسين السلوك المشكل لأطفالهم - محمد، صلاح الدين عراقي Mohammed, Salahuldin Iraqi (رابطة التربويين العرب, 2014)
استهدفت الدراسة الحالية تبين فاعلية تدريب الوالدين (الأمهات) على استراتيجيات (النشطة والتفاعلية) برنامج تحليل سلوك تطبيقي في تحسين سلوك أطفالهم المشكل. وقد تم تطبيق مقياس السلوك المشكل للأطفال (إعداد الباحث، 2013) على مجموعة من الأمهات بلغ عددهن 64 أما تراوحت أعمارهن بين 35- 39 عاماً بمتوسط 37.5 عاماً وانحراف معياري 10 شهور وفترة زواج تراوحت بين 11-15 عاماً لديهن أطفالاً في مرحلة التعليم الابتدائي تراوحت أعمارهن بين 6- 9 سنوات بمتوسط 8.2 عاماً وكانت الأمهات ملتحقات في برنامج الدراسات العليا بكلية التربية جامعة بنها في الدبلوم العام والعامين والمهني والخاص. وبعد تصحيح مقياس السلوك المشكل للأطفال (في ضوء تقرير الأمهات) تم بشكل عشوائي اختيار عدد 36 من الأمهات اللاتي قررن وجود سلوك مشكل مرتفع لدي أطفالهن وتوزيعهم بشكل عشوائي إلى مجموعتين تجريبية (13 أماً) ومجموعة ضابطة (13 أماً). وتم تطبيق برنامج تحليل السلوك التطبيقي (إعداد الباحث) على أمهات المجموعة التجريبية (14 جلسة بمعدل جلسة أسبوعياً للجلسات الإثنى عشر الأول والجلستان الأخيرتان في الأسبوع الأخير). ثم تم تطبيق مقياس السلوك المشكل للأطفال على أمهات المجموعتين التجريبية والضابطة بعد الانتهاء من جلسات برنامج تحليل السلوك التطبيقي لتبين فاعليته في تحسين السلوك المشكل لأطفال أمهات المجموعة التجريبية مقارنة بأبطال أمهات المجموعة الضابطة (للتحقق من الفرض الأول للدراسة). كما تم إعادة تطبيق مقياس السلوك المشكل للأطفال على أمهات المجموعة التجريبية بعد شهرين من الانتهاء من تطبيق برنامج تحليل السلوك التطبيقي لتبين استمرار فاعليته في فترة المتابعة (للتحقق من الفرض الثاني للدراسة). وقد أوضحت النتائج فاعلية تدريب أمهات المجموعة التجريبية على استخدام أدوات الاستراتيجيات النشطة والتفاعلية في برنامج تحليل السلوك التطبيقي واكتسابهن مهارات تطبيقها مع أطفالهن في البيئة الطبيعية وتحسين سلوكهم المشكل بعد تطبيق البرنامج مقارنة بأطفال أمهات المجموعة الضابطة وفي فترة المتابعة. وتم مناقشة النتائج في ضوء الإطار النظري والدراسات والبحوث السابقة، كما تم اقتراح أفكار بحثية في ضوء نتائج هذه الدراسة والتوصية بدارستها.
Current study targeted shows the effectiveness training of parents (mothers) strategies (active and proractive) applied behavior analysis program (ABA)to improve their children's conduct behavior. Has been applied to measure the behavior problem children (prepared by the researcher, 2013) on a group of mothers was their number 64 The ages ranged between 35 ~ 39 years with an average of 37.5 years and a SD. 10 months and the period of marriage ranged between 11~15 years, they have children in primary education between the ages of 6 ~ 9 years with an average of 8.2 years. The mothers were in the postgraduate program at the Faculty of Education, University of Banha in general one year diploma and two years, professional and private. Having responded scale behavior problem children (in the light of the report of mothers) were randomly choose the number 26 of the mothers who had decided the presence of the behavior problem is high among their children, and distributed randomly into two groups: experimental (13) and a control group (13). was applied of (ABA)program (prepared by the researcher) on the mothers of the experimental group (14 meetings, with an average session per week for sessions twelve first and sessions last two in the last week), then been applied to measure the behavior problem of children on mothers experimental and control groups after the completion sessions(ABA)to show its effectiveness in improving the behavior problem of their children of the experimental group compared to children of mothers of the control group (to verify the first hypothesis of the study), has also been re-apply the measure of behavior problem children to the mothers of the experimental group, after two months the completion of the application(ABA)program to show continued effectiveness in the follow-up period (to verify the second hypothesis of the study). Results showed the effectiveness of the training of the mothers of the experimental group on the use of tools strategies, active and proactive of (ABA)program and acquired skills applied with their children in the natural environment and improve their behavior problem after the application of the program than children of mothers at the control group and in the follow-up period. Was discussion of the results in light of the theoretical framework and previous studies and research, as has been proposed research ideas in the light of the results of this study and recommendation for studying it. Keywords: Applied behavior analysis - a behavioral intervention - behavior problem - a training program for mothers.
Keywords: مستخلصات الأبحاث -- البرامج التدريبية -- الصحة النفسية -- التحليل النفسي -- السلوك التطبيقي -- البرامج التدريبية -- الأمهات